Zur Kenntnis der Collembolen in der Paläarktis (Insecta, Entognatha). - Dunger, Wolfram (Contributions to Entomology = Beiträge zur Entomologie, 2006)
A survey of Palaearctic Collembola has never been published so far. Taxonomical and faunistical papers of the last decades brought about a sharp increase of the knowledge for the European and Asiatic regions as well. Since 1994, the author edites the “Synopses on Palaearctic Collembola” at the State Museum of Natural History Görlitz as a precursor of a Palaearctic Fauna. So far, four volumes appeared (Hypogastruridae, Tullbergiinae, Isotomidae, Symphypleona). 57% of the species of these supertaxa were described later than 1960, and 47% are mainly distributed in the asiatic part of Palaearctis. The total number of Palaearctic species can be estimated as 3100. The paper informs about problems in Collembolan taxonomy and shows the plan of edition of the “Synopses” up to 2010.KeywordsCollembola, species numbers, taxonomy, Palaearctis.